Cardiovascular Risk in Psoriatic Patients Detected by Heart Rate Variability (HRV) Analysis. (November 2014) - Proietti, Ilaria; Raimondi, Gianfranco; Skroza, Nevena; Pampena, Riccardo; Bernardini, Nicoletta; La Viola, Giorgio; Nicolucci, Francesca; Tolino, Ersilia; Zuber, Sara; Scordamaglia, Beatrice; Balduzzi, Veronica; Soccodato, Valentina; et al.
Abstract: Postmarketing Phase IV Patients affected by severe psoriasis have an increased prevalence of cardiovascular () diseases as documented by several studies. Heart rate variability (HRV) is a noninvasive method to evaluate the autonomic control of the sinus node. In this study, HRV analysis has been used to evaluate whether young patients with moderate cutaneous psoriasis have increased cardiovascular (CV) risk, in absence of CV comorbidities. Our data indicate an imbalance toward the sympathetic arm of the autonomic cardiac modulation. As the increase in sympathetic activity may be associated with a higher CV risk, moderate psoriasis could be considered to be an independent CV risk factor.